2010
DOI: 10.2119/molmed.2010.00063
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Extracellular Signal-Regulated Kinase (ERK)-1/2 Is Associated with the Downregulation of Peroxisome Proliferator-Activated Receptor (PPAR)-γ during Polymicrobial Sepsis

Abstract: Peroxisome proliferator-activated receptor (PPAR)-γ is a ligand-activated transcription factor and regulates inflammation. Posttranslational modifications regulate the function of PPARγ, potentially affecting inflammation. PPARγ contains a mitogen-activated protein kinase (MAPK) site, and phosphorylation by extracellular signal-regulated kinase (ERK)-1/2 leads to inhibition of PPARγ. This study investigated the kinetics of PPARγ expression and activation in parenchymal and immune cells in sepsis using the MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…These results provide the first direct evidence that AdipoR1 may function as a CTRP9 binding protein. Recently, studies on knockout mice indicate that the two receptors mediate different signaling events in liver, with AdipoR1 primarily acting on AMPK, and AdipoR2 primarily affecting PPARα, 36, 39,40 consistent with our study’s mechanistic data. The adapter protein APPL1, containing a pleckstrin homology domain, a phosphotyrosine-binding domain, and a leucine zipper motif, appears to be a key intracellular effector of adiponectin’s effects, via binding to the N-terminus of AdipoR1.…”
Section: Discussionsupporting
confidence: 90%
“…These results provide the first direct evidence that AdipoR1 may function as a CTRP9 binding protein. Recently, studies on knockout mice indicate that the two receptors mediate different signaling events in liver, with AdipoR1 primarily acting on AMPK, and AdipoR2 primarily affecting PPARα, 36, 39,40 consistent with our study’s mechanistic data. The adapter protein APPL1, containing a pleckstrin homology domain, a phosphotyrosine-binding domain, and a leucine zipper motif, appears to be a key intracellular effector of adiponectin’s effects, via binding to the N-terminus of AdipoR1.…”
Section: Discussionsupporting
confidence: 90%
“…For example, hypoxia activates mitogen-activated protein kinases (MAPKs) [17, 18] that regulate the activity of transcription factors such as PPARγ and NF-κB. Hypoxia also activates pro-inflammatory and oxidative stress signals that reduce PPARγ expression and activity [19, 20]. Hypoxia selectively increased Nox4 expression in the pulmonary vasculature [21].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the mechanism of action of the combined treatment, we evaluated the lung nuclear activation of pERK1/2, an important mitogen-activated protein kinase that has been postulated to have a pathological role in sepsis also by mediating PPARγ degradation (15). At Western blot analysis, expression of the active pERK1/2 slightly increased in lung nuclear extracts 18 h after laparotomy (sham) and was significantly enhanced by CLP procedure when compared to baseline expression of control normal mice.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these previous studies, we found that combined treatment of zinc supplementation and C-peptide restored lung nuclear expression of PPARγ, which was associated with a remarkable inhibition of NF-κB activity and subsequent downregulation of the NF-κB dependent pro-inflammatory cytokines, TNF-α and IL-6, and the chemokine MIP-1α. To further define the anti-inflammatory molecular mechanisms of zinc supplementation of C-peptide we also investigated the role of ERK1/2, which have been implicated in the regulation of pro-inflammatory transcription factors and in the pathogenetic events of sepsis (15). In vitro studies in cultured cells have also suggested that ERK1/2 activation may result into PPARγ inactivation, as the kinases induce PPARγ phosphorylation, thus triggering the nuclear receptor for protein degradation (34).…”
Section: Discussionmentioning
confidence: 99%